1995
DOI: 10.2466/pr0.1995.76.3.1019
|View full text |Cite
|
Sign up to set email alerts
|

Type A/B Behavior and Eight Basic Emotions in 1084 Employees

Abstract: We examined the prevalence of Type A/B behavior and Emotion Profiles in 1084 employees. This report focused on the relationship between Type A behavior and eight basic emotion dimensions. Of the 1084 subjects 710 (65%) scored as Type A and 374 (34.5%) as Type B. The mean Bortner scores for all subjects were 182.8 (SD = 33.7), scores on emotional dimensions for Incorporation and Reproduction were high, and intensities for Ejection and Destruction were low; mean scores on other emotions were normal. Significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Despite this lack of research addressing this relationship, related research exists. For instance, in a study of the relationship between global TABP and eight basic emotion dimensions, Type A individuals tended to be significantly less trusting, controlled, and timid, and more distrustful, uncontrolled, and aggressive than Type B individuals (Catipovic-Veselica et al, 1995). Similar findings were obtained by Malatesta-Magai, Jonas, Shepard, and Culver (1992), who found that Type As scored significantly higher than Type Bs on measures of anger and aggression, and showed greater inhibition and shame regarding the expression of their anger.…”
Section: Type a Behaviour Patternsupporting
confidence: 55%
“…Despite this lack of research addressing this relationship, related research exists. For instance, in a study of the relationship between global TABP and eight basic emotion dimensions, Type A individuals tended to be significantly less trusting, controlled, and timid, and more distrustful, uncontrolled, and aggressive than Type B individuals (Catipovic-Veselica et al, 1995). Similar findings were obtained by Malatesta-Magai, Jonas, Shepard, and Culver (1992), who found that Type As scored significantly higher than Type Bs on measures of anger and aggression, and showed greater inhibition and shame regarding the expression of their anger.…”
Section: Type a Behaviour Patternsupporting
confidence: 55%
“…Thus, it is a high level of expressed anger and hostility, not the other elements of Type A behavior, which constitute the problem (17). Individuals, who were classified as Type A pattern, had ratings lower on trustful, controlled, and timid, and higher on aggressive, distrustful and uncontrolled behaviors than Type B pattern (18). Lombardo and Carreno (19) demonstrated that Type As' alveolar carbon monoxide (COa) levels were higher than Type Bs', and Jenkins Activity Survey scores were correlated with COa and their findings revealed that Type As and Type Bs did not differ in number of puffs taken or puff volume, but Type As' inhalation duration was 70% longer than Type Bs'.…”
Section: Introductionmentioning
confidence: 95%
“…(table continues) Culver, 1993;Catipovic-Veselica et al, 1995); Anger inhibition and anger bound to shame (Malatesta-Magai et al, 1993); Heightened levels of hostile attitudes (Weekes & Waterhouse, 1991); Higher levels of anger proneness (Suzuki & Haruki, 1994); High negative emotions during hospitalization (Wrzesniewski, Debska, & Tyminska-Sedek, 1994) Elevated aggressiveness is a result of the lack of integration within the ego. There is a lack of cohesion between the aggression and the more positive feelings within the psyche.…”
Section: Understanding Via Ps Positionmentioning
confidence: 99%
“…Higher levels of distrust (Catipovic-Veselica et al, 1995); Heightened suspiciousness (Kunen & Stamps, 1991) It is not surprising that distrust should arise when the object has been imbued with the aggression of the ego. The object that is so perceived cannot be properly trusted.…”
Section: Understanding Via Ps Positionmentioning
confidence: 99%